Exploring School Counseling Experiences Concerning Teachers’ Involvement in School Counseling: A Qualitative Study - Satyal, Shrijana (NPRC Journal of Multidisciplinary Research, 2025)
The intervention of school teachers in counseling is explored based on the perceptions and experiences of both school counselors and teachers. This qualitative study also aims to differentiate the roles of counselors in school from that of school teachers. The experience of teacher’s intervention by the counselors are focused to understand during the study. The study collected data through in-depth interviews with two school counselors and two school teachers from different schools of Kathmandu, Nepal. Thematic analysis revealed four key themes: “Antibiotic vs. Therapy,” “Rays of Hope,” “Collaboration Helps,” and “Delineate the Roles.” The findings highlight the challenges counselors face due to the teacher’s quick fix mentality, the positive impact of collaboration, and the importance of counselor’s ethics. The study concludes that aligning teachers’ expectation with counselor’s ethics, collaboration be fostered and role definition should be well established in order to create a supportive school environment that promotes academic upgrades and learner’s well-being.